Repeated radon exposure induced lung injury and epithelial–mesenchymal transition through the PI3K/AKT/mTOR pathway in human bronchial epithelial cells and mice. (1st November 2020) - Chen, Huiqin; Chen, Na; Li, Fengsheng; Sun, Liang; Du, Jicong; Chen, Yuanyuan; Cheng, Fei; Li, Yanqing; Tian, Siqi; Jiang, Qisheng; Cui, Fengmei; Tu, Yu
Highlights: Repeated radon exposure reduced the cell adhesion, promoted the cell proliferation and invasion in 16HBE and BEAS-2B cells. Repeated radon exposure induced epithelial–mesenchymal transition (EMT) in epithelial cells and mice. Repeated radon exposure induced lung damage and pulmonary fibrosis in mice. The lung injury and EMT induced by radon involved the PI3K/AKT/mTOR signaling pathway. Abstract: Radon exposure is the most frequent cause of lung cancer in non-smokers. The high linear energy transfer alpha-particles from radon decay cause the accumulation of multiple genetic changes and lead to cancer development. Epithelial–mesenchymal transition (EMT) plays an important role in oncogenesis. However, the mechanisms underlying chronic radon exposure-induced EMT attributed to carcinogenesis are not understood. This study aimed to explore the EMT and potential molecular mechanisms induced by repeated radon exposure. The EMT model of 16HBE and BEAS-2B cells was established with radon exposure (20000 Bq/m 3, 20 min each time every 3 days). We found repeated radon exposure facilitated epithelial cell migration, proliferation, reduced cell adhesion and ability to undergo EMT through a decrease in epithelial markers and an increase in mesenchymal markers. Radon regulated the expression of matrix metalloproteinase 2 (MMP2) and tissue inhibitors of metalloproteinase 2 (TIMP2) to disrupt the balance of MMP2/TIMP2. In vivo, BALB/c mice were exposed to 10 5 Bq/m 3 radon gas for cumulative doses of 60 and 120 Working Level Months (WLM). Radon inhalation caused lung damage and fibrosis in mice, which was aggravated with the increase of exposure dose. EMT-like transformation also occurred in lung tissues of radon-exposure mice. Moreover, radon radiation increased p-PI3K, p-AKT and p-mTOR in cells and mice. Radon reduced the GSK-3β level and elevated the active β-catenin in 16HBE cells. The m-TOR and AKT inhibitors attenuated radon exposure-induced EMT by regulation related biomarkers. These data demonstrated that radon exposure induced EMT through the PI3K/AKT/mTOR pathway in epithelial cells and lung tissue.